Penyuluhan, Peragaan Pembuatan Pangan Fungsional Berbahan Kelor (Moringa oleifera) Untuk Pencegahan Stunting Di Kelurahan Kemirimuka, Kecamatan Beji, Depok - Albert Jackson Yang; Fri Rahmawati; Maria Bintang; Marina Silalahi (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
Stunting is still a major nutritional problem faced by the Indonesian people. From the results of the previous PKM, in RW 17 Kemirimuka there were still cases of stunting 11.11% of toddlers who attended the activity. One effort that can be made to reduce the incidence of stunting is to provide functional foods such as Moringa leaves (Moringa oleifera). Moringa leaves have high vitamin C, calcium, beta-carotene, potassium and protein content, this PKM aims to provide counseling, demonstration of making functional food from Moringa leaves and anthropometric measurements in monitoring the nutritional status of toddlers at Posyandu Cempaka RW 17 Kemirimuka Village, Beji District, Depok. The 4-stage counseling method is a lecture, demonstration of making pudding from Moringa, filling out a questionnaire about the organoleptic of pudding, and measuring the anthropometry of toddlers. Based on filling out the questionnaire, it is known that making pudding from Moringa leaves is easy to do with simple and easily obtained ingredients, has a delicious taste and an attractive shape so that it is liked by toddlers. The results of anthropometric measurements show that most toddlers at Posyandu Cempaka RW 17, Kemirimuka Village, Beji District, Depok City-West Java have good (normal) nutrition and no toddler respondents were found to have poor/bad nutrition and there was no stunting. Keywords: Kemirimuka Village, Moringa, Stunting